2016
DOI: 10.4081/ijfs.2016.5793
|View full text |Cite
|
Sign up to set email alerts
|

Influence of incubation conditions on biofilm formation by Pseudomonas fluorescens isolated from dairy products and dairy manufacturing plants

Abstract: In this study, biofilm formation of 64 Pseudomonas fluorescens strains isolated from milk, dairy products and dairy plants was compared. The strains were grown on Tryptic Soy Broth supplemented with 0.2% of glucose, on polystyrene microplates at 10 and 30°C for 48 h. In general, 57/64 P. fluorescens strains formed biofilm, although with great variability at both tested temperatures. Moreover, our results evidenced that the biofilm-forming ability of the strains was temperature- and strain-dependent. Interestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 22 publications
1
38
0
Order By: Relevance
“…Thus, we suggest on day three, a large number of bacteria in the plate were switched to biofilm. An optimum number of bacteria adherence occurred in microtiter plate resulting strong biofilm formation on that day (Jama et al 2017;Rossi et al 2016). In addition to day three, we observed that the biofilm formation by P. aeruginosa and S. pyogenes were strong on days four, five and six.…”
Section: Resultssupporting
confidence: 58%
“…Thus, we suggest on day three, a large number of bacteria in the plate were switched to biofilm. An optimum number of bacteria adherence occurred in microtiter plate resulting strong biofilm formation on that day (Jama et al 2017;Rossi et al 2016). In addition to day three, we observed that the biofilm formation by P. aeruginosa and S. pyogenes were strong on days four, five and six.…”
Section: Resultssupporting
confidence: 58%
“…Indeed, P. fluorescens has the ability to adapt even to hostile environments, e.g., cold rooms, where the conditions for its growth are not optimal [3,4]. The ability of these microorganisms to adapt to different environments is likely accounted for by the formation of biofilms, making the bacterial population very resistant [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…This proves that after the extended incubation, the biofilm formed on the peg lids have more time to recruit more bacteria in the biofilm establishing denser and larger colony on EMB agar. [32] Within 24 hrs, concentrations 1:1 and 2:3 both exhibited pinpoint colonies in quadrants I, II and III while showed small colonies in quadrant IV. Concentration 1.5:3.5 produced small colonies in quadrants I, II and III whereas medium colonies in quadrant IV.…”
Section: Resultsmentioning
confidence: 95%
“…This proves that as the incubation prolongs, it gives more time for the bacteria to aggregate and combine with one another constructing one large colony. [32] Colonies also gave slightly pink appearance owing to its capability to ferment glucose due to the presence of E. coli and these appeared to be mucoid due to the extracellular polysaccharide matrix produced during the biofilm formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation